Hubungan Stone Burden dengan Penurunan Hemoglobin Pasca Operasi Percutaneous Nephrolithotomy di RSUP DR. M. Djamil Padang - Millenia Calista; Yevri Zulfiqar; Rina Gustia (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Kidney stones are one of the three most common cases in urology. The best standard management for kidney stones with stone burden >20mm is PCNL (percutaneous nephrolithotomy), a minimal invasive method that uses percutaneous access to remove stones. One of the most complications was bleeding which can be caused by several factors , one of them is stone burden.Objective. to look at the relationship of stone burden with hemoglobin drop after PCNL in patients with renal stoneMethods. This study is an analytical study with retrospective approach towards all patients diagnosed with kidney stones and treated with PCNL at RSUP Dr. M. Djamil Padang at based on patient medical record data. Data analysis used Chi square tests where the relationship between variables is said to be significant if p value <0.05Results. Data showed that from 65 kidney stone patients treated with PCNL, the highest prevalence were men and the most age group are 45-64 years. The most types of stones are staghorn and the highest stone burden is 20 - ≤30 mm. Some cases with the involvement of hydronephrosis with an average length of stay <5 days. Hemoglobin drop mean in kidney stones ≤2gr / dL. Statistical analysis showed that there is no relationship between stone burden and hemoglobin drop after PCNL in kidney stone patients (p value = 0,706).Conclusion. The conclusion of this studied is that there is no significant relationship between stone burden with hemoglobin drop after PCNL in patients with kidney stone.